Seeking missing pieces in learning about single slit diffraction: results from a teacher survey - Mešić, Vanes; Škaljo, Edvin; Mitrevski, Boce; Nešić, Ljubiša; Hatibović, Senad; Maličević, Mevludin (IOP Publishing, 2021)
Single slit diffraction is part of many high-school physics curricula throughout the world. In this study, we aimed to investigate whether high-school physics teachers from Bosnia and Herzegovina, Serbia and North Macedonia are adequately prepared to discuss with their students about various aspects of the single slit diffraction pattern, particularly about vertical length of diffraction fringes. To that end we conducted a written survey which included 57 high-school physics teachers. Besides asking teachers about students' difficulties in learning about single slit diffraction, we also asked them to specify their own difficulties with this topic and required them to solve a conceptual task. Almost every second teacher believed that vertical length of diffraction fringes can be increased by changing shape or width of the slit and only 1 out of 57 teachers managed to correctly answer why diffraction fringes become shorter when we move away from the central maximum. We concluded that physics teacher education programmes should be changed to develop understanding of both, horizontal and vertical aspects of the diffraction pattern. To that end it is useful to provide learning opportunities which encourage combining ray and wave model of light.